A placebo-controlled, double-blind clinical trial to evaluate the efficacy of Imedeen® Time Perfection® for improving the appearance of photodamaged skin - Stephens TJ; Sigler ML; Herndon Jr JH; Dispensa L; Le Moigne A (Dove Medical Press, 2016)
Thomas J Stephens,1 Monya L Sigler,1 James H Herndon Jr,2 Lisa Dispensa,3 Anne Le Moigne3 1Thomas J. Stephens and Associates, Inc., Richardson, TX, 2Dermatology Center of Dallas, Dallas, TX, 3Pfizer Consumer Healthcare, Madison, NJ, USA Objective: To assess the efficacy of Imedeen Time Perfection for improving the appearance and condition of photoaged skin in healthy women. Methods: This randomized, double-blind, placebo-controlled clinical trial enrolled healthy women, 35–60 years of age, with Fitzpatrick I–III and Glogau II–III skin types and mild-to-moderate facial fine lines/wrinkles. The eligible subjects were randomized to receive two tablets daily of either Imedeen Time Perfection (Imedeen) or a matching placebo for 12 weeks. Efficacy assessments included investigator rating of 16 photoaging parameters (ie, global facial appearance and 15 individual facial parameters and the average of all parameters), instrumentation (ie, ultrasound dermal density, moisture level of the stratum corneum, transepidermal water loss, cutometry), and subjects' self-assessment. Differences in the mean change from baseline to week 12 values on these outcomes were compared between Imedeen and placebo using analysis of variance or a paired t-test. Results: Seventy-four subjects with primarily Fitzpatrick skin type III (78%–79%) and Glogau type III (53%–58%) completed the study (Imedeen: n=36; placebo: n=38). The mean difference in change from baseline to week 12 for global facial assessment significantly favored Imedeen over placebo (−0.52; P=0.0017). Additionally, the mean differences in the average of all facial photoaging parameters (−0.29), mottled hyperpigmentation (−0.25), tactile laxity (−0.24), dullness (−0.47), and tactile roughness (−0.62) significantly favored Imedeen over placebo (P≤0.05). Significantly greater increases in ultrasound dermal density (+11% vs +1%; P≤0.05) and stratum corneum moisturization (+30% vs +6%; P≤0.05) were also observed for Imedeen than for placebo. There were no significant differences on other instrumental outcomes. Conclusion: The results of this study suggest that Imedeen Time Perfection can positively affect the appearance of photoaged skin, moisturization, and skin density over 12 weeks of treatment. Keywords: photoaging, dietary supplement, marine complex